PENGARUH KREDIT TERHADAP KESEJAHTERAAN PETANI CABAI RAWIT MERAH DI KABUPATEN TASIKMALAYA - Puspitasari, Anisa; Novianty, Ane; Aziz, Saepul (Universitas Galuh Ciamis, 2021)
Agricultural goods which include capital goods can be in the form of money, land, fertilizer, investment in machinery. Credit acts as a capital increase to finance production inputs so that producers can increase their products at a higher level, chili is one of the commodities that have bright prospects to increase farmers' income. in the area. The sampling technique using the accidental sampling technique is a sampling technique based on chance, ie anyone who meets by chance with the researcher can be used as a sample, if the farmer met is suitable as a data source Because the population is too large and the author has limited time, funds, and energy, the sample in this study was deliberately determined, namely 30 respondents from all cayenne pepper farmers who use credit for their agriculture. The analysis technique is carried out using multiple linear regression analysis, where the data is processed using SPSS. The results of this study indicate the regression coefficient of equity (X1) -493 has a negative effect on changes in income levels, but not significant. The regression coefficient for agricultural credit loans (X2) 566 has a positive and significant effect on changes in income levels. From the results of the calculation of the regression coefficient of land area (X3) 183,866 that the magnitude of the influence of the independent variable X3 (land area) on changes in the income level of chili farmers has a positive effect. The conclusion of this study is that chili farmers who make credit loans are expected to build or increase the income and welfare level of their debtors from the agricultural sector.